Pulmonary Tuberculosis in a Child with Mediastinal Inflammatory Myofibroblastic Tumor : a Rare Case: A Literature Review - Siti Wahyu Windarti (Journal of Diverse Medical Research: Medicosphere, 2025)
Background : Tuberculosis is one of the most important global health problems in children. Mediastinal masses in pediatric age patients have a wide range of differential diagnoses, including benign and malign tumors and chronic infectious process. Mediastinal mass is a rare presentation of tuberculosis in children. Objective : To report a rare case of pulmonary tuberculosis in a child with mediastinal inflammatory myofibroblastic tumor. Case Report : A 4 year 2 month-old boy with chief complaint of cough since less than one month before admission. The cough accompanied with greenish yellow sputum, no coughing of blood, the cough during morning, noon, or night, and did not affected by cold air and there were no causative factors causing of coughing. The coughing did not improve by taking medication. The patient also complained of shortness of breathing since three days before admission accompanied by chest pain in the right side. The initial examination of the patient alert with a weakness of general condition and dypneu. Anthropometric examination obtained patient weight 13 kg, height 97 cm (WAZ =-2, LAZ >-2, WLZ > -2, WHO Child Growth Standards). Laboratory result on admission were leukocytes 10.120/uL, hemoglobin 11,3g/dL, hematocrit 36,9%, trombocyte 517.000, BUN 5mg/dL, SCr 0,36mg/dL, ALT 46U/L, AST 41U/L, Na 136nmol/L, K 4,3mmol/L, Cl 104mmol/L, Ca 8,7mmol/L, CRP 14,8mg/L. The thoracic MSCT result showed the tuberculosis process. The Gene X-pert examination revealed MTB detected positive rifampicin susceptable The guiding Thoracic CT Scan FNAB result showed mediastinal mass with size 4.6 x 5.5 cm (benign spindle mesenchymal tumor, according with inflammatory myofibroblastic tumor). The patient given first line tuberculosis treatment, for a while the mediastinal inflammatory myofibroblastic tumor not be treated, will be reevaluated after the tuberculosis treatment was completed. Conclusions : This case report describes a pulmonary tuberculosis with mediatinal inflammatory myofibroblastic tumor